4-Hydr-oxy-3-nitro-benzaldehyde. - Rizal, M.R.; Azizul, I.; Ng, S.W. (International Union of Crystallography, 2008)
The hydroxyl group in each of the two independent mol-ecules of the title compound, C(7)H(5)NO(4), participates in two O-H⋯O hydrogen bonds, viz. one intra-molecular bond to the nitro group and one inter-molecular bond to the aldehyde group of the same mol-ecule in the next unit, resulting in a linear chain structure. The dihedral angle between the aromatic ring and the nitro group is 10.9 (3)° in one mol-ecule and 9.9 (2)° in the other.